Safeguards Assessment-2019 Update - Kabwe, George (Policy Papers; Policy Paper ;, 2019)
Safeguards assessments are a key pillar of the risk management arrangements for IMF lending. Safeguards assessments aim to mitigate the risks of misuse of Fund resources and misreporting of program monetary data under Fund arrangements. Safeguards assessment reports are confidential and therefore the IMF Executive Board is provided with a periodic report on safeguards activities on a biennial basis, in addition to high-level summaries in member country staff reports on key findings and recommendations. This update on safeguards activity covers the period May 2017 to end-April 2019 (the period).